2018
DOI: 10.1111/and.13214
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella vulgaris ameliorates testicular toxicity induced by deltamethrin in male rats via modulating oxidative stress

Abstract: This study was carried out to investigate the potential effects of Chlorella vulgaris (CV) on testicular function and oxidant/antioxidant status in normal and deltamethrin‐intoxicated rats. Forty adult male rats were drenched either with normal saline, CV (50 mg/kg), deltamethrin (DM) (3 mg/kg), or CV combined with DM, daily for 8 weeks. At the end of the protocol, the epididymal sperm quality was evaluated and the testicular superoxide dismutase (SOD), catalase enzyme (CAT) and malondialdehyde (MDA), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
(94 reference statements)
3
11
0
Order By: Relevance
“…The antioxidant property of CV might counteract and prevent the negative, disruptive effect of oxidative stress on spermatogenesis, male reproductive hormonal profiles, and hypothalamic–pituitary–gonadal axis. These results are consistent with those of the previous studies (Bansal & Bilaspuri, 2010; Osama et al., 2018). Supplementation with a source of polyunsaturated fatty acids (PUFAs) like commercial algal product found to improve the sperm count and motility (Khoshvaght et al, 2016; Murphy et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The antioxidant property of CV might counteract and prevent the negative, disruptive effect of oxidative stress on spermatogenesis, male reproductive hormonal profiles, and hypothalamic–pituitary–gonadal axis. These results are consistent with those of the previous studies (Bansal & Bilaspuri, 2010; Osama et al., 2018). Supplementation with a source of polyunsaturated fatty acids (PUFAs) like commercial algal product found to improve the sperm count and motility (Khoshvaght et al, 2016; Murphy et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…The healing effect of CV could be attributed to its powerful antioxidant activities with subsequently associated reduced inflammatory condition; the current findings were supported by data of Osama et al. (2018).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Zari and Al-Attar (2011) showed that treatment of male rats with CBZ resulted in severe damage and completely absences of spermatogonia, primary spermatocytes, secondary spermatocytes, spermatids and spermatozoa and losses of the spermatogenesis process. Moreover, adverse reproductive effects attributed to pesticides, including their effect on fertility, have also been well established in various experimental studies ( Hassan and Meligi, 2017 , El-Demerdash et al, 2019 , Ghorbani Taherdehi et al, 2019 , Osama et al, 2019 )…”
Section: Discussionmentioning
confidence: 97%